Optimizing Rooftop Solar Panel Deployment: A GIS-Based Analysis at KFUPM - Hidayat, Ikhsan (MUSTEK ANIM HA, 2024)
The Geographic Information System (GIS) factor determines optimal panel placement and orientation for maximizing sunlight exposure and energy generation efficiency. However, the uneven roof characteristics of some buildings like Building 18 KFUPM can result in less efficient placement of solar panels and reduce the potential for solar energy production. This is due to shadows cast by the uneven roof relief, which may obstruct direct sunlight exposure to the solar panels during certain periods of the day. Additionally, this study explores the design and implementation of solar photovoltaic (PV) systems, emphasizing meticulous component selection to optimize performance and efficiency. Key components such as the Sunny Tripower 24000TL-US inverter by SMA and Trina Solar TSM-PD14 320 modules were chosen for their reliability and advanced technology. Through detailed simulations and analyses, the system's design parameters and energy generation potential are evaluated. This installation, comprising 8,205 solar panels, is projected to generate 5,078 GWh annually, marking a significant step towards sustainability goals. Notably, among the ten assessed buildings, capacities range from 27.2 kW to 505.0 kW, highlighting the scale and impact of this project.